Morphological insights into the degradation of perovskite solar cells under light and humidity - Sun, Kun; Guo, Renjun; Liang, Yuxin; Heger, Julian E.; Liu, Shangpu; Yin, Shanshan; Reus, Manuel A.; Spanier, Lukas V.; Deschler, Felix; Bernstorff, Sigrid; Müller-Buschbaum, Peter (ACS applied materials & interfaces, 2023)
Perovskite solar cells (PSCs) have achieved competitive power conversion efficiencies compared with established solar cell technologies. However, their operational stability under different external stimuli is limited, and the underlying mechanisms are not fully understood. In particular, an understanding of degradation mechanisms from a morphology perspective during device operation is missing. Herein, we investigate the operational stability of PSCs with CsI bulk modification and a CsI-modified buried interface under AM 1.5G illumination and 75 ± 5% relative humidity, respectively, and concomitantly probe the morphology evolution with grazing-incidence small-angle X-ray scattering. We find that volume expansion within perovskite grains, induced by water incorporation, initiates the degradation of PSCs under light and humidity and leads to the degradation of device performance, in particular, the fill factor and short-circuit current. However, PSCs with modified buried interface degrade faster, which is ascribed to grain fragmentation and increased grain boundaries. In addition, we reveal a slight lattice expansion and PL redshifts in both PSCs after exposure to light and humidity. Our detailed insights from a buried microstructure perspective on the degradation mechanisms under light and humidity are essential for extending the operational stability of PSCs.
Online veröffentlicht: 16. Juni 2023
Gesehen am 09.08.2023